Balance between Hyperinflammation and Immunosuppression in Sepsis - Yadav, Hemang; Cartin-Ceba, Rodrigo (Seminars in Respiratory and Critical Care Medicine, 2016)
Sepsis is a major cause of morbidity and mortality among hospitalized patients and the leading cause of death among patients admitted to intensive care units. The immune response in sepsis is characterized by the activation of both proinflammatory and anti-inflammatory pathways. These pathways are concurrent, starting early in the course of sepsis. Given the high burden of morbidity and mortality associated with sepsis, there is an increasing interest in immunomodulatory therapies targeted at improving outcomes in sepsis. This review will summarize current understanding about the balance between hyperinflammation and immunosuppression in sepsis and discuss the role of potential therapies to modulate these responses.
Keywords: sepsis; immunology; immunosuppression; glucocorticoid